2013
DOI: 10.5101/nml.v5i2.p129-134
|View full text |Cite
|
Sign up to set email alerts
|

Surface Texturing of TiO2 Film by Mist Deposition of TiO2 Nanoparticles

Abstract: Unique and various microstructures of titanium oxide (TiO2) film including macroporous structure, chromatic veins and rings, have been easily fabricated by mist deposition method on silicon substrate with mild preparation conditions. Rutile phase TiO2 nanoparticles were directly used as starting material to prepare film and led to a simple preparation process. It was found that several different microstructures existed in the sample and changed with the varied positions from the center to the edge of the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However, only a few studies about employing the mist-assisted deposition method for functional thin films using NP dispersions have been reported. Watanabe 35 and Kim 36 et al reported the preparation of porous TiO 2 films from preheated and dried spray mists, respectively. More recently, we demonstrated the preparation of gallium-doped zinc oxide (GZO) on glass substrates as TCO thin films by the GZO NP-mist deposition method 37 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies about employing the mist-assisted deposition method for functional thin films using NP dispersions have been reported. Watanabe 35 and Kim 36 et al reported the preparation of porous TiO 2 films from preheated and dried spray mists, respectively. More recently, we demonstrated the preparation of gallium-doped zinc oxide (GZO) on glass substrates as TCO thin films by the GZO NP-mist deposition method 37 .…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies about employing the mist-assisted deposition method for functional thin lms using NP dispersions have been reported. Watanabe [35] and Kim [36] et al reported the preparation of porous TiO 2 lms from preheated and dried spray mists, respectively. More recently, we demonstrated the preparation of galliumdoped zinc oxide (GZO) on glass substrates as TCO thin lms by the GZO NP-mist deposition method.…”
Section: Introductionmentioning
confidence: 99%